Foundations of nursing - White, Lois; Baumle, Wendy; Duncan, Gena (Cengage Learning, 2011)
Provides comprehensive information necessary to successfully complete a practical or vocational nursing curriculum, including basic nursing, adult health nursing and material and pediatric nursing. This book covers the health care system, communication, nursing processes, and client teaching, as well as topics such as HIPAA and bioterrorism